Spontaneous Symptomatic Pseudoarthrosis at the L2-L3 Intervertebral Space with Diffuse Idiopathic Skeletal Hyperostosis: A Case Report. (5th November 2013) - Hasegawa, Keiji; Takahashi, Hiroshi; Iida, Yasuaki; Yokoyama, Yuichirou; Fukutake, Katsunori; Takamatsu, Ryo; Nakamura, Kazumasa; Suzuki, Daisuke; Shishikura, Wataru; Tsuge, Shintaro; Sekiguchi, Masayuki; Wada, Akihito
Abstract : Pseudoarthrosis at the intervertebral space in patients with ankylosing spondylitis has occasionally been reported, but symptomatic pseudoarthrosis at the intervertebral disc level is rare in patients with diffuse idiopathic skeletal hyperostosis (DISH). Here, we report a case of symptomatic pseudoarthrosis at the L2-L3 intervertebral space that was diagnosed based on clinical history. We first performed L1–L5 fixation, but back-out of the pedicle screw occurred in the early postoperative phase and may have been caused by a short fixation range and concomitant Parkinson's disease. However, the prognosis of the case was favorable after a second surgery. This case indicates that a fixation range of at least 3 above and 3 below is necessary for bone fracture of a thoracolumbar vertebra and pseudoarthrosis in patients with DISH.